2015
DOI: 10.1149/2.0731508jes
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Magnesium Electrodeposition from Glyme-Coordinated Ammonium Amide Electrolytes

Abstract: We prepared less volatile and halide-free electrolytes for room temperature non-dendritic magnesium (Mg) electrodeposition by mixing a Mg 2+ -amide-containing ionic liquid (IL) with equimolar glyme (Mg 2+ +IL : glyme = 1:1). Raman spectroscopy suggested that in the equimolar mixture most glyme molecules are coordinated to Mg 2+ cations and/or IL cations, which is also supported by a single crystal X-ray diffraction study. The glyme-coordinated IL electrolytes showed sizable redox currents (order of mA cm -2 ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 42 publications
4
35
1
Order By: Relevance
“…Also, the charge‐delocalized framework makes this conjugated [NTf 2 ] − anion highly resistant to positive potential polarization, and thus high anodic stability can be expected in such electrolytes. There have been a number of studies using Mg[NTf 2 ] 2 in different solvents for reversible Mg electrochemistry, particularly in polyether(s) ,. Electrolytes using 0.5 M Mg[NTf 2 ] 2 in a glyme/diglyme mixture showed a high conductivity of 5.2 mS cm −1 , and the anodic stability on stainless steel (SS) substrate was up to 4.2 V vs Mg …”
Section: Rechargeable Mg Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the charge‐delocalized framework makes this conjugated [NTf 2 ] − anion highly resistant to positive potential polarization, and thus high anodic stability can be expected in such electrolytes. There have been a number of studies using Mg[NTf 2 ] 2 in different solvents for reversible Mg electrochemistry, particularly in polyether(s) ,. Electrolytes using 0.5 M Mg[NTf 2 ] 2 in a glyme/diglyme mixture showed a high conductivity of 5.2 mS cm −1 , and the anodic stability on stainless steel (SS) substrate was up to 4.2 V vs Mg …”
Section: Rechargeable Mg Batteriesmentioning
confidence: 99%
“…There have been a number of studies using Mg[NTf 2 ] 2 in different solvents for reversible Mg electrochemistry, particularly in polyether(s). [43,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] Electrolytes using 0.5 M Mg[NTf 2 ] 2 in a glyme/diglyme mixture showed a high conductivity of 5.2 mS cm À1 , and the anodic stability on stainless steel (SS) substrate was up to 4.2 V vs Mg. [46] Glymes with higher oligomer degree exhibit stronger ability to solvate Mg[NTf 2 ] 2 . [43,51] For example, a higher solubility of Mg has been reported in tetraglyme (G4) than in diglyme (G2).…”
Section: Mg[ntf 2 ] 2 Electrolytesmentioning
confidence: 99%
“…A uniform smooth thin film of Mg was achieved and no dendritic growth was observed. Although, other ex situ studies indicated non dendrite growth 10 30 31 , this work provides the first in situ study to support the theoretical prediction that Mg batteries should not have safety related issues imposed by dendritic growth 20 .…”
Section: Resultsmentioning
confidence: 51%
“…Ionic liquids (ILs), or room temperature molten salts, are possible additives for Mg-ion batteries because of their dual role as electrolyte and solvent, large windows of voltage stability, low volatility and inability to ignite. [12][13][14] Some of the inherent limitations of ILs are high viscosities, low transference numbers and low conductivities which can be mitigated with cosolvents like THF [15][16][17][18][19] and glycol ethers [20,21]. Cosolvents with ILs have also been suggested to promote Mg 2+ dissociation [22] because Mg electrodeposition and dissolution from pure ILs with magnesium salts has been difficult [15,[23][24][25] or poorly reproducible [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…[15] Kitada et al studied the oxidative stability of electrolytes with IL, glyme and magnesium bis[(trifluoromethyl)sulfonyl]amide salt and determined that the IL/glyme mixtures had a higher oxidative stability than IL-free electrolytes with only glyme solvent. [20] They attributed the improved stability to the lack of free glymes in solution when an IL is also present.…”
Section: Introductionmentioning
confidence: 99%